Electrode for water electrolysis and preparation method and application thereof
By using inverse opal structure and Ir-supported catalyst in the water electrolytic electrode, the problem of excessive loading of precious metals is solved, efficient and low-cost water electrolytic reaction is achieved, and the stability and catalytic activity of the electrode are improved.
Patent Information
- Application Number
- CN202411852244.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the existing water electrolysis technology, the high load of precious metals leads to high costs and unstable performance, especially the mass transfer loss under large currents, which affects the electrolytic efficiency.
The inverse opal structure formed by orderly assembly of monodisperse sphere polystyrene microspheres is used as the electrode material, and Ir is loaded through cyclic volt electrodeposition technology to construct a catalyst with high specific surface area and good diffusion properties.
It realizes efficient electrolytic water reaction under a small applied bias voltage, reduces the load of precious metals, improves catalytic activity and stability, and reduces the corrosion of the gas diffusion layer.
Smart Images

Figure HDA0005190885640000011 
Figure HDA0005190885640000012 
Figure HDA0005190885640000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis, and in particular relates to an electrode for water electrolysis and a preparation method and application thereof. Background Art
[0002] In 1966, proton exchange membrane (PEM) was first used by General Electric Company for water electrolysis. Water electrolysis provides a clean conversion route from water to hydrogen. If renewable energy is used to produce electricity for water electrolysis, zero CO2 emissions can be truly achieved. The basic principle of hydrogen production by water electrolysis is to use external electrical energy to decompose water into hydrogen and oxygen. In theory, the cathode and anode need to apply theoretical electromotive forces of 0 and 1.23V respectively, but due to the existence of polarization, a voltage greater than 1.23V is actually required to make the water electrolysis reaction occur. During the electrolysis process, water molecules are oxidized into oxygen at the anode and reduced to hydrogen at the cathode.
[0003] Unfortunately, expensive precious metals, perfluorosulfonic acid membranes, gas diffusion layers, bipolar plates and other components increase the cost of PEMWE, seriously hindering its commercial application. Therefore, it is necessary to reduce the cost of PEMWE from multiple angles and aspects, and improve the performance of PEMWE. This is also one of the current focuses of researchers. The core of the electrolysis process is the membrane electrode required for the electrochemical reaction, which directly affects the electrolysis efficiency, electrolysis energy consumption, electrolysis cost and the life of the electrolytic cell.
[0004] At the same time, the gas diffusion layer titanium felt also has the following problems: 1. The internal pore structure of the titanium fiber felt is randomly distributed. When the reactant water (H2O) and the reaction product oxygen bubbles (O2) are transferred inside it, greater resistance will be generated. Especially under large currents, mass transfer losses will be more obvious, thus affecting the electrolysis efficiency; 2. Due to the random distribution of the pore structure on the surface of the titanium fiber felt, there are fewer electrochemical reaction sites at the three-phase connection, which greatly limits the speed and efficiency of the electrolysis reaction and makes the entire electrolysis process inefficient; 3. In order to maintain the conductivity of the titanium felt, it is necessary to plate precious metals such as platinum and iridium on the surface of the titanium felt. This not only increases the production cost, but also makes the titanium coating unstable and has problems such as shedding. Summary of the invention
[0005] The purpose of the present invention is to provide an electrode for water electrolysis and a preparation method and application thereof, which overcomes the problem of excessive loading of precious metals in traditional electrodes, while ensuring that the electrode prepared according to the method enables the water electrolysis reaction to be carried out efficiently under a smaller external bias voltage.
[0006] The present invention utilizes a template formed by orderly assembling monodisperse spherical polystyrene microspheres, and after filling the gaps of the template with a substance, the template is removed to obtain a porous structure with a highly ordered periodicity and a pore interconnection system, which is an inverse opal structure. The evaporation self-assembly method is used to control the synthesis of an ordered oxygen evolution electrode with uniform size and good dispersion under relatively mild conditions. The catalyst can still maintain its original appearance after calcination and has good thermal stability. The inverse opal structure has a continuous nanostructure skeleton with a large interface area and a three-dimensional interconnected pore system with low curvature. Titanium felt is considered to be the best transmission layer for PEMWE due to its high porosity and the corrosion resistance of the Ti surface passivation layer under oxidizing conditions. The electrode prepared by the inverse opal structure has a highly ordered pore structure, good catalyst dispersibility and excellent diffusion performance, which enables a relatively low noble metal load to obtain a higher catalytic activity. The present invention introduces the inverse opal structure into the electrode, constructs the inverse opal structure on the titanium felt, and uses the cyclic voltaic electrodeposition technology to load Ir to establish a good gas transmission channel while also having good catalyst activity and stability, and can better prevent the corrosion of the gas diffusion layer.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] In one aspect, the present invention provides an electrode for water electrolysis, the electrode comprising a gas diffusion layer and a catalyst, wherein the catalyst is supported on the gas diffusion layer;
[0009] The catalyst is Ir-coated RuO2, and the catalyst is an inverse opal structure;
[0010] The gas diffusion layer is titanium felt.
[0011] In the above technical solution, further, the outer pore diameter of the catalyst is 100-600nm, the inner pore diameter is 82-470nm, and the pore wall thickness is 25-50nm; in the catalyst, the mass ratio of Ir element to Ru element is 1:1.2-1.8.
[0012] Another aspect of the present invention provides a method for preparing the above-mentioned oxygen evolution electrode, comprising the following steps:
[0013] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water in sequence, and drying;
[0014] (2) adding a nonionic surfactant and polystyrene microspheres to water, ultrasonicating to obtain a dispersion, placing the titanium felt obtained in step (1) into the dispersion, and drying until the liquid is completely volatilized to obtain a titanium felt having a 3D template;
[0015] (3) vacuum drying the titanium felt with the 3D template obtained in step (2);
[0016] (4) placing the titanium felt with the 3D template after drying in step (3) in an aqueous solution of RuCl3 for the first electrodeposition, drying, and then calcining to obtain a titanium felt loaded with RuO2 in an inverse opal structure;
[0017] (5) Placing the inverse opal structure RuO2-loaded titanium felt obtained in step (4) in an aqueous solution of IrCl4 for a second electrodeposition, followed by annealing in an inert gas atmosphere to obtain the electrode.
[0018] In the above technical solution, further, in step (1), each ultrasonic treatment lasts for 15 to 30 minutes.
[0019] In the above technical scheme, further, in step (2), the diameter of the polystyrene microspheres is 50 to 500 nm; the mass ratio of the nonionic surfactant to the polystyrene microspheres is 1:(0.8 to 1.6), more preferably 1:1.2; the ultrasonic time is 30 to 60 min; the nonionic surfactant is nonylphenol polyoxyethylene ether; and the drying temperature is 65 to 80°C.
[0020] In the above technical solution, further, in step (3), the vacuum drying temperature is 50 to 80° C., and the vacuum drying time is 6 to 12 hours.
[0021] In the above technical solution, further, in step (4), the first electrodeposition is constant current electrodeposition, the electrodeposition time is 100 to 400 s, and the current density is -10 to -30 mA cm -2 ; The calcination temperature is 400-450°C and the calcination time is 2-3h.
[0022] In the above technical solution, further, in step (5), the second electrodeposition adopts cyclic voltammetry electrodeposition, the cyclic voltammetry voltage is -0.7 to 0.2VSCE, and the number of cyclic voltammetry cycles is 25 to 100 times.
[0023] In the above technical solution, further, in step (5), the annealing temperature is 400-450° C., and the annealing time is 2-3 hours.
[0024] The present invention also provides an application of the above oxygen evolution electrode, wherein the oxygen evolution electrode is used as an oxygen evolution catalyst in a photoelectrocatalytic water electrolysis reaction, an AEM water electrolysis cell or an acidic water electrolysis hydrogen generator.
[0025] The beneficial effects of the present invention are:
[0026] 1. The oxygen evolution electrode with a porous inverse opal structure having different pore sizes provided by the present invention has an inverse opal ordered nanoarray with a large specific surface area, which can expose more active sites and increase the active sites in contact with the electrolyte, thereby enhancing its charge transmission capacity. At the same time, the Ir coating greatly curbs the dissolution of Ru. The porous structure with different pore sizes can provide additional gas-liquid transmission channels. The catalyst has good stability. By regulating its structure, the surface area is increased to achieve the purpose of increasing its active sites.
[0027] 2. The preparation method of the present invention can effectively regulate the morphology of the product by controlling the reaction conditions and preparation parameters, and synthesize porous interconnected holes (i.e., inverse opal structure) with uniform morphology and good dispersion. The holes of the porous structure formed by the action of polystyrene microspheres of different sizes also show obvious differences. The hole size and pore wall thickness will also have a significant impact on the stability of its structure and the activity of the catalyst. In addition, the self-assembly and electrodeposition technology used in this application is relatively simple in process, low in cost, and easy to realize industrial production. It can effectively control the synthesis of electrodes under relatively mild conditions.
[0028] 3. Compared with nanoarrays such as nanorods and nanotubes, the inverse opal structure catalyst prepared by the method of the present invention has a higher specific surface area and oxygen evolution catalytic activity. The external bias required for decomposing water to produce hydrogen in a water electrolysis cell is smaller, and it has better stability. The prepared electrode has good performance when used as an oxygen evolution electrode for PEM acidic water electrolysis to produce hydrogen. At the same time, it has a wide range of utilization value in renewable fuel cells (RFCs), photoelectrocatalytic water electrolysis reactions, and electrolytic hydrogen generator devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the titanium felt with a 3D template prepared in Example 1, a is 1 μm, b is 100 nm;
[0030] Figure 2 TEM image of the titanium felt with 3D template prepared in Example 1, a is 50 nm, b is 100 nm, c is 300 nm, and d is 500 nm;
[0031] Figure 3 This is a morphology diagram of the oxygen evolution electrode prepared in Example 1;
[0032] Figure 4 The stability test results of the oxygen evolution electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 3 are shown;
[0033] Figure 5 The polarization curves obtained by linear voltammetric scanning of the oxygen evolution electrode prepared in Example 2 are shown in Examples 1-4;
[0034] Figure 6 Polarization curves obtained by linear voltammetric scanning of the oxygen evolution electrodes prepared in Example 1 and Examples 5-6;
[0035] Figure 7 Polarization curves obtained by linear voltammetric scanning of the oxygen evolution electrodes prepared in Example 1 and Examples 7-9. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be further described below with reference to the accompanying drawings, including the preparation method, characteristics and applications of the electrode for water electrolysis, but the protection scope of the present invention shall not be limited thereto.
[0037] Example 1
[0038] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0039] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a polystyrene microsphere dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0040] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0041] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80°C for 3 h and then calcined in a tube furnace at 400°C for 3 h in an air atmosphere to obtain a titanium felt loaded with RuO2 in an inverse opal structure.
[0042] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the inverse opal structure RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4, and cycled 100 times at (-0.7 to 0.2 V) VS SCE, and then annealed at 450° C. for 3 h in an argon atmosphere in a tubular furnace to obtain an electrode.
[0043] like Figure 1-2As shown in Figure 2, polystyrene microspheres were successfully loaded on the surface of titanium felt to form a multi-layered and well-defined layered structure, as shown in Figure 2. Figure 3 As shown, after the noble metal is loaded and the template is removed, it is found that a porous and well-defined inverse opal structure can be well formed. In this structure, the outer pore diameter is 357 nm, the inner pore diameter is 323 nm, and the pore wall thickness is 32 nm.
[0044] Example 2
[0045] The same preparation process as in Example 1 was adopted, except that the diameter of the polystyrene microspheres was 50 nm.
[0046] Example 3
[0047] The same preparation process as in Example 1 was adopted, except that the diameter of the polystyrene microspheres was 100 nm.
[0048] Example 4
[0049] The same preparation process as in Example 1 was adopted, except that the diameter of the polystyrene microspheres was 500 nm.
[0050] Example 5
[0051] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0052] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.24 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a polystyrene microsphere dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0053] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0054] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80°C for 3 h and then calcined in a tube furnace at 400°C for 3 h in an air atmosphere to obtain a titanium felt loaded with RuO2 in an inverse opal structure.
[0055] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the inverse opal structure RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4 and cycled 100 times at (-0.7 to 0.2 V) VS SCE, followed by annealing at 450° C. for 3 h in a tube furnace with argon atmosphere to obtain an electrode.
[0056] Example 6
[0057] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0058] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.48 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, and placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized to obtain a titanium felt having a 3D template;
[0059] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0060] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80 °C for 3 h, and then calcined in a tube furnace at 400 °C for 3 h in an air atmosphere to obtain RuO2-loaded titanium felt.
[0061] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4 and cycled 100 times at (-0.7 to 0.2 V) VS SCE, followed by annealing at 450° C. for 3 h in a tube furnace with argon atmosphere to obtain an electrode.
[0062] Example 7
[0063] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0064] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0065] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0066] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80°C for 3 h and then calcined in a tube furnace at 400°C for 3 h in an air atmosphere to obtain a titanium felt loaded with RuO2 in an inverse opal structure.
[0067] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the inverse opal structure RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4 and cycled at (-0.7 to 0.2 V) VS SCE for 75 times, followed by annealing at 450° C. for 3 h in a tubular furnace with argon atmosphere to obtain an electrode.
[0068] Example 8
[0069] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0070] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0071] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0072] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80°C for 3 h and then calcined in a tube furnace at 400°C for 3 h to obtain an inverse opal structure RuO2-loaded titanium felt.
[0073] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4 at (-0.7 to 0.2 V) VS SCE for 50 cycles, followed by annealing at 450° C. for 3 h in a tubular furnace under an argon atmosphere to obtain an electrode.
[0074] Example 9
[0075] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0076] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0077] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0078] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80 °C for 3 h and then calcined in a tube furnace at 400 °C for 3 h in an air atmosphere to obtain RuO2-loaded titanium felt.
[0079] (5) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the RuO2-loaded titanium felt obtained in step (4) was placed in an aqueous solution of IrCl4 and cycled 25 times at (-0.7 to 0.2 V) VS SCE, followed by annealing at 450° C. for 3 h in a tubular furnace under an argon atmosphere to obtain an electrode.
[0080] Comparative Example 1
[0081] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0082] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0083] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0084] (4) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the titanium felt with the 3D template obtained in step (3) was placed in an aqueous solution of IrCl4, with the titanium felt as a working electrode, a graphite sheet electrode (4 cm*4 cm) as a counter electrode, and a saturated calomel electrode (SCE) as a reference electrode. The reaction was cycled 100 times at (-0.7 to 0.2 V) VS SCE, and then annealed at 450°C for 3 h in a tubular furnace with argon atmosphere to obtain an electrode.
[0085] Comparative Example 2
[0086] (1) The titanium felt was cleaned with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min each, thereby removing impurities and oil stains on the surface of the titanium felt, and then dried in a vacuum drying oven at 65°C;
[0087] (2) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt obtained in step (1) was placed in the RuCl3 aqueous solution, with the titanium felt as the working electrode, a graphite sheet electrode (4 cm*4 cm) as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode at -10 mA cm -2 After the preparation, the sample was placed in a vacuum drying oven at 80 °C for 3 h and then calcined in a tube furnace at 400 °C for 3 h.
[0088] (3) 0.167 g of iridium tetrachloride was dissolved in 100 mL of deionized water, and the sample obtained in step (2) was placed in an aqueous solution of IrCl4 and cycled 100 times at (-0.7 to 0.2 V) VS SCE for secondary electrodeposition. Subsequently, an argon atmosphere was introduced into a tubular furnace and annealed at 450° C. for 3 h to obtain an electrode.
[0089] Comparative Example 3
[0090] (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water for 15 min respectively to remove impurities and oil stains on the surface of the titanium felt, and drying;
[0091] (2) adding 0.3 g of nonionic surfactant nonylphenol polyoxyethylene ether (NP-40) and 0.36 g of polystyrene microspheres (with a diameter of 300 nm) into 100 ml of deionized water, and ultrasonicating for 30 min to obtain a dispersion, placing the titanium felt obtained in step (1) into the polystyrene microsphere dispersion, and drying at 65° C. until the liquid is completely volatilized, to obtain a titanium felt having a 3D template;
[0092] (3) drying the titanium felt with the 3D template obtained in step (2) in a vacuum drying oven at 60° C. for 6 h;
[0093] (4) 0.38 g of RuCl3 was dissolved in 75 mL of deionized water and stirred for 3 h. The titanium felt with the 3D template after drying in step (3) was placed in an aqueous solution of RuCl3. The titanium felt with the 3D template was used as a working electrode, a graphite sheet electrode (4 cm*4 cm) was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode at -10 mA cm -2 After the preparation is completed, the sample is placed in a vacuum drying oven at 80°C for 3 h and then calcined in a tube furnace at 400°C for 3 h to obtain an electrode.
[0094] Electrochemical tests were performed on the electrodes prepared in Examples 1-9 and Comparative Examples 1-3. Half-cell tests were performed in a three-electrode system at room temperature, with a saturated calomel electrode (SCE) as the reference electrode, graphite as the counter electrode, 0.5M H2SO4 solution as the electrolyte, and a 30°C water bath.
[0095] The electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 3 were tested, and the experimental results showed that in the stability test, Example 1> Comparative Example 1> Comparative Example 3, indicating that the Ir coating has a good effect on improving the stability.
[0096] The stability test of the electrodes prepared in Examples 1-4 and Comparative Example 2 was performed as follows: Figure 5As shown in the figure, the structure loaded with 300nm polystyrene microspheres has more excellent performance advantages. Compared with the electrode without inverse opal structure, its stability is greatly improved. This can be attributed to the fact that the inverse opal ordered nanoarray has a larger specific surface area, which can expose more active sites and increase the contact active sites with the electrolyte, thereby enhancing its charge transfer ability. At the same time, the Ir coating greatly curbs the dissolution of Ru, and the macroporous structure can provide additional gas-liquid transmission channels.
[0097] The polarization curves obtained by linear voltammetric scanning of electrodes prepared with different polystyrene microsphere contents in Examples 1 and 5-6 are as follows: Figure 6 As shown in the figure, within a certain range of proportions, as the content of polystyrene microspheres increases, the electrode performance is significantly improved.
[0098] The polarization curves obtained by linear voltammetric scanning of the electrodes prepared at different cycle times in Example 1 and Examples 7-9 are as follows: Figure 7 As shown, the results show that within a certain range of CV times, increasing the CV times can significantly improve the electrode performance, indicating that the Ru coating is getting better and better, and the synergistic effect between Ir and RuO2 is enhanced.
[0099] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. An electrode for water electrolysis, characterized in that: The electrode comprises a gas diffusion layer and a catalyst, wherein the catalyst is supported on the gas diffusion layer; The catalyst is Ir-coated RuO2, and the catalyst is an inverse opal structure; The gas diffusion layer is titanium felt.
2. The electrode for water electrolysis according to claim 1, characterized in that: The outer pore diameter of the catalyst is 100-600 nm, the inner pore diameter is 82-470 nm, and the pore wall thickness is 25-50 nm; in the catalyst, the mass ratio of Ir element to Ru element is 1:(1.2-1.8).
3. A method for preparing an electrode for water electrolysis according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) ultrasonically cleaning the titanium felt with acetone, dilute hydrochloric acid, ethanol and deionized water in sequence, and drying; (2) adding a nonionic surfactant and polystyrene microspheres to water, ultrasonicating to obtain a dispersion, placing the titanium felt obtained in step (1) into the dispersion, and drying until the liquid is completely volatilized to obtain a titanium felt having a 3D template; (3) vacuum drying the titanium felt with the 3D template obtained in step (2); (4) placing the titanium felt with the 3D template after drying in step (3) in an aqueous solution of RuCl3 for the first electrodeposition, drying, and then calcining to obtain a titanium felt loaded with RuO2 in an inverse opal structure; (5) Placing the inverse opal structure RuO2-loaded titanium felt obtained in step (4) in an aqueous solution of IrCl4 for a second electrodeposition, followed by annealing in an inert gas atmosphere to obtain the electrode.
4. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (1), each ultrasonic treatment lasts for 15 to 30 minutes.
5. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (2), the diameter of the polystyrene microspheres is 50 to 500 nm; The mass ratio of the nonionic surfactant to the polystyrene microspheres is 1:(0.8-1.6); The ultrasonic time is 30 to 60 minutes; The nonionic surfactant is nonylphenol polyoxyethylene ether; The drying temperature is 65-80°C.
6. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (3), the vacuum drying temperature is 50 to 80° C., and the vacuum drying time is 6 to 12 hours.
7. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (4), the first electrodeposition is constant current electrodeposition, the electrodeposition time is 100 to 400 s, and the current density is -10 to -30 mA cm -2 ; The calcination temperature is 400-450° C., and the calcination time is 2-3 hours.
8. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (5), the second electrodeposition adopts cyclic voltammetry electrodeposition, the cyclic voltammetry voltage is -0.7 to 0.2VSCE, and the number of cyclic voltammetry cycles is 25 to 100 times.
9. The method for preparing an electrode for water electrolysis according to claim 3, characterized in that: In step (5), the annealing temperature is 400-450° C., and the annealing time is 2-3 hours.
10. Use of an electrode for water electrolysis according to any one of claims 1 to 2 or an electrode prepared by the method for preparing an electrode for water electrolysis according to any one of claims 3 to 9, characterized in that: The electrode is used as an oxygen evolution electrode in a photoelectrocatalytic water electrolysis reaction, an AEM water electrolysis cell or an acidic water electrolysis hydrogen generator.
Citation Information
Patent Citations
Electrocatalytic electrode having ditungsten carbide (W2C) inverse opal composite micro-nano structure, preparation and hydrogen evolution application thereof
CN110129814A
Electrocatalytic electrode with WP-nickel hydroxide inverse opal composite micro-nano structure and preparation method and hydrogen evolution application thereof
CN110512230A
Titanium fiber felt anode diffusion layer for PEM water electrolysis tank as well as preparation method and application thereof
CN112647086A
Supported iridium-based catalyst thin layer and preparation method thereof
CN114481196A
Anode diffusion layer electrode for PEM electrolyzed water as well as preparation method and application of anode diffusion layer electrode
CN117248232A